Evaluation of coronary artery risk factors in premenopausal women (<45 years): a single-center prospective study - Shinde, Alok Suresh; Shukla, Anand Narendra; Dixit, Priyadarshini Mahadev (International Journal of Research in Medical Sciences, 2021)
Background: The present study was designed to evaluate the association of conventional coronary risk factors in the angiographically proven cases of younger women (<45 years) with significant CAD along with clinical profile and coronary angiographic findings. Methods: This was a hospital-based prospective study conducted at a tertiary-care center in India. A total of 200 premenopausal women (age ≤45 years) who presented with chest pain likely to be of cardiac origin were enrolled. Each patient was subjected to routine clinical investigations, examination of complete lipid profile, follicular stimulating hormone (FSH), luteinizing hormone (LH), and prolactin; and underwent non-invasive cardiac examination and coronary angiography. Results: Mean age of patients was 39.1±4.98 years. A total of 64 (32%) patients had history of spontaneous abortions and 80 (40%) patients presented with ST-elevated myocardial infarction. Increased FSH, LH and prolactin levels was found in 70 (35%), 20 (10%), and 88 (44%) patients, respectively. Total 196 (98%) patients underwent coronary angiography which revealed presence of significant CAD in 122 (63%) cases and of which 80 patients underwent coronary angioplasty and 12 underwent coronary artery bypass grafting. Of all, 8 death were reported up to the mean follow-up of 11 months. Conclusions: The study stated that premenopausal females (<45 years) represent a special subgroup where non-conventional risk factors play an important role in occurrence of CAD. So, careful history taking with detailed menstrual and obstetric history should be considered in such group of patients.